2005
DOI: 10.1128/aem.71.5.2331-2337.2005
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Forms of Selenium in the Metal-Resistant Bacterium Ralstonia metallidurans CH34 Exposed to Selenite andSelenate

Abstract: Ralstonia metallidurans CH34, a soil bacterium resistant to a variety of metals, is known to reduce selenite to intracellular granules of elemental selenium (Se 0 ). We have studied the kinetics of selenite (Se IV ) and selenate (Se VI ) accumulation and used X-ray absorption spectroscopy to identify the accumulated form of selenate, as well as possible chemical intermediates during the transformation of these two oxyanions. When introduced during the lag phase, the presence of selenite increased the duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
82
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 30 publications
11
82
1
1
Order By: Relevance
“…Figure 2 shows the normalized Se K-edge XANES spectra collected for a selection of model compounds with characteristic selenium valences. The Se K-edge position is sensitive to the valence of Se [3,[7][8][9][10]. In contrast to previous studies, no simple relation is found between the Se K-edge position and the selenium valence.…”
Section: Xafs Spectroscopycontrasting
confidence: 52%
See 1 more Smart Citation
“…Figure 2 shows the normalized Se K-edge XANES spectra collected for a selection of model compounds with characteristic selenium valences. The Se K-edge position is sensitive to the valence of Se [3,[7][8][9][10]. In contrast to previous studies, no simple relation is found between the Se K-edge position and the selenium valence.…”
Section: Xafs Spectroscopycontrasting
confidence: 52%
“…Biological processes for the removal of soluble selenium were mainly described for different natural inocula (soil and sediments) from which most of the bacteria able to reduce selenate or selenite were isolated [1,2]. The end products of this reduction are manifold, including elemental selenium, hydrogen and metal selenides but also organo-selenium compounds (Se amino acids and volatile compounds) [3]. Selenium bioreduction in the treatment of mining effluents and agricultural drainage waters and the capacity of biological selenate removal of anaerobic granular sludge biofilms harboring numerous bacterial strains has been recently investigated in batch conditions [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In a few species of bacteria, selenate and selenite act as electron acceptors in an anaerobic form of respiration (16,33,34), whereas for most of the microorganisms studied so far, reduction of selenium oxyanions is not a bioenergetic process. Some species, including E. coli (36), Thauera selenatis (4,29), and Enterobacter cloacae SLD1a-1 (15), have been reported to reduce both selenate and selenite; others, like R. sphaeroides (38) and Ralstonia metallidurans (28), can only reduce selenite.…”
mentioning
confidence: 99%
“…In addition, various sequences were related to bacteria able to reduce a variety of elements and compounds, including ( et al, 1989;Wang et al, 1990;Rege et al, 1997); (v) selenium oxyanions, such as Enterobacter cloacae (Watts et al, 2003;Losi and Frankenberger, 1997;Ridley et al, 2006;Yee et al, 2007) and Ralstonia sp. (Valls et al, 2000;Sarret et al, 2005);and (vi) arsenic, such as Flavobacterium sp. (Macur et al, 2004).…”
Section: Laboratory-scale Bioreactormentioning
confidence: 99%